Paraneoplastic Leukemoid Reaction after Primary Tumor Resection in Patients with Urothelial Carcinoma: A Report of 2 Cases - Shien-Tung Pan; Shu-Ping Tseng; Chiou-Huey Wang; Yu-Ting Chou (SAGE Publishing, 2021)
Leukemoid reaction (LR), which is defined as leukocytosis with a white blood cell (WBC) count above 50 000/µL, can be caused by various conditions, while paraneoplastic leukemoid reaction (PLR), a rare type of paraneoplastic syndrome, occurs in cases of solid tumors. Here we report 2 cases of high-grade urothelial carcinoma (HGUC) with PLR accompanied by rapid tumor progression after complete resection of the primary tumor. We reviewed the patient's clinical history, histopathology, and the results of laboratory tests to rule out LR induced by non-tumor causes. In both cases, PLR appeared after primary tumor resection, and the patients died of disease at the peak of PLR at 6 and 8 weeks. Immunohistochemistry for granulocyte colony-stimulating factor and its receptor was performed on tumor tissues. Patients with HGUC and PLR are rare and have an extremely poor prognosis. The mechanism by which solid tumors are associated with PLR and rapid tumor progression after surgical resection of the primary tumor is incompletely understood and will be discussed here.